Cystic Pleomorphic Adenoma: A Rare Occurrence and a Diagnostic Pitfall - Khan, Shujaat; Parveen Choudhary; Priyanka Yadav; Yadav, Nitesh Kumari; Parveen, Shahnaz (Annals of Pathology and Laboratory Medicine, 2025)
Background: Cystic lesions of the salivary glands are a diagnostic dilemma. Pleomorphic adenoma, the most common neoplasm of the salivary gland, with cyst formation, is a rare event and can mimic various benign and malignant lesions. Case report: Here, we report an interesting case of a 25-year-old male with cystic degeneration of pleomorphic adenoma. Conclusion: Cyst formation in the salivary gland is not only seen in several cyst-associated lesions but can also be seen rarely in cyst-unassociated lesions like pleomorphic adenoma. Appropriate cytodiagnosis and optimal management of such cystic lesions require the application of the Milan System for Reporting Salivary Gland Cytopathology (MSRSGC).